Use of transcriptomic analysis to identify microRNAs related to the effect of stress on thymus immune function in a chicken stress model. (November 2021) - Tian, Huihui; Ding, Mengxia; Guo, Yujie; Su, Aru; Zhai, Minxi; Tian, Yadong; Li, Kui; Sun, Guirong; Jiang, Ruirui; Han, Ruili; Kang, Xiangtao; Yan, Fengbin
Abstract: In modern poultry production, stress-induced immunosuppression leads to serious economic losses and harm to animals, but the molecular mechanisms governing the effects of stress on the chicken thymus have not been elucidated. In this study, we successfully constructed a stress model of 7-day-old Gushi chickens by adding exogenous corticosterone (CORT) to their diet and determined the microRNA (miRNA) expression profile of thymus tissues using RNA-seq technology. The results identified 51 differentially expressed miRNAs (DEMs), including 30 upregulated miRNAs and 21 downregulated miRNAs. A total of 164 target genes of the DEMs were predicted based on bioinformatic analysis methods, and Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses of these target genes were performed. The results from the GO enrichment analysis of the target genes identified 349 significantly enriched terms, including terms associated with the stress response and immune function that are primarily involved in the negative regulation of phagocytosis, the response to stress and the cellular response to stimulus. The KEGG pathway analysis indicated that the enriched pathways related to immunity or stress included the MAPK signaling pathway, lysosomes, endocytosis, and the RIG-I-like receptor signaling pathway. Among these pathways, DEMs (such as gga-miR-2954, gga-miR-106-5p, and gga-miR-16-5p) and corresponding target genes (such as IL11Ra, SIKE1, and CX3CL1 ) might be strongly correlated with thymic immunity in chickens. The results of this study provide a reference for further research on the molecular regulatory mechanisms governing the effect of stress on the immune function of the chicken thymus. Highlights: A CORT-induced stress model was constructed to explore the effect of stress on immune function of the chicken thymus. A total of 51 DEMs were obtained by RNA-seq and a total of 164 target genes of DEMs were predicted. miR-2954, miR-106-5p, miR-16-5p and IL11Ra, SIKE1, CX3CL1 have a strong correlation with the thymic immunity in chickens.